The ‘Theodosian Code’ laws on exile - Silva, Érica Cristhyane Morais da (Romanitas - Revista de Estudos Grecolatinos, 2019)
Exile has always been a form of punishment adopted by the ancient Romans. In the Republic and in the context of the Principate there are several cases of banning senators. In late antiquity, we have almost no news of cases of senatorial exile. The most evident, most explored and studied exiles in this context are the cases of episcopal banishment, especially during the rule of Constantius II (337-361). Nevertheless, senatorial exiles continued to occur even in the context of Late Antiquity although these have not been the subject of historian’s study. On Theodosian Code, we did not find accurate evidence on senatorial exiles except for 14, 10, 3, on military clothing used inappropriately, which specifically mentions the use of military clothing by senators which is prohibited by this statute. Nevertheless, even with sparse evidence, on the senatorial exile, we will dedicate ourselves in this paper to reflect on the exiles as presented in Theodosian Code in order to understand senatorial exiles as part of the banishment phenomenon in Late Antiquity.
Keywords: Late Antiquity; Exile; Senate; Theodosian Code